Analisis Rantai Nilai Usaha Produk Rengginang UMKM Kabupaten Bogor - Prisca Nurmala Sari (Journal of Management and Business Review)
The business of rengginang is potential enough to be developed in Bogor Regency. But, the SMEs (Small and Medium Enterprises) actors feel that the margin which is accepted is very low. So that, the research about the value chain of rengginang in Bogor Regency should be conducted. The aims of this research are analyzing the value chain of rengginang business and generating the recommendation for SMEs in order to increase the margin.  This research was conducted in Bogor regency using a qualitative method and Porter Value Chain Model. This research was using 55 SMEs as respondents. The sample was determined by purposive sampling method. The results show that from the primary activities of rengginang side, there were only inbound logistics and operation activities which were having a role and contribution in increasing margin (value added) of rengginang. While from the support activities of rengginang side, there were no activities which were contributing in increasing of rengginang’s margin. It can be concluded that the margin or profit of rengginang SMEs was low because not all activities in the value chain model can contribute to increase the margin of rengginang products. The SMEs can maximize all of their activities in value chain and also by selling the rengginang product in cooked condition and in many variation. It can be a strategy to win a competition.